The SnackerTracker: A novel home-cage monitoring device for measuring food-intake and food-seeking behaviour in mice [version 2; peer review: 2 approved] - Vladyslav Vyazovskiy; Keiran Foster; Zoltán Molnár; Stuart Peirson; Marissa Mueller; Carina Pothecary; Selma Tir; Laurence Brown; Elise Meijer (Wellcome Open Research)
Background Accurately measuring activity and feeding is important in laboratory animal research, whether for welfare-monitoring or experimental recording. Quantification commonly involves manual pellet-weighing; however, this can physically disturb animals and cannot continuously assess both the amount and pattern of feeding over time. Improved means of food-intake measurement have been developed but can be costly and incompatible with many cage configurations. Methods We developed the SnackerTracker—a novel home-cage monitoring system which continuously records food-intake, food-seeking activity, and ambient light conditions in laboratory mice. After benchtop validations, we tested this device by recording from C57BL/6J control mice under 12:12h light:dark (LD) and constant darkness (DD) to measure circadian rhythms in feeding behaviour. We then recorded from mice having disturbed circadian rhythms (cryptochrome 1 and 2 double-knockouts, Cry1-/-,Cry2-/- ), where irregular activity and feeding patterns were expected. Animals were individually housed with SnackerTrackers in Digital Ventilated Cages® (DVC, Tecniplast) to measure home cage activity. After habituation, 48-hour SnackerTracker and DVC recordings were collected and compared. Results The SnackerTracker accurately measured food-masses throughout benchtop and in vivo validation tests. Time-course SnackerTracker feeding traces correlated well with DVC activity recordings, indicating that feeding reflects general cage locomotion in control and cryptochrome-deficient animals. In LD, SnackerTracker data showed expected feeding/fasting cycles in control and cryptochrome-deficient animals yet reduced dark-phase feeding in cryptochrome-deficient mice. In DD, increased feeding during the subjective nighttime was maintained in control animals but abolished in cryptochrome-deficient mice. Surprisingly, cryptochrome-deficient animals exhibited ultradian feeding rhythms. Conclusions We validate the performance and value of monitoring home cage feeding using the SnackerTracker. Here we show that cryptochrome-deficient animals have decreased food-intake in LD, diurnal arrhythmicity in DD, and ultradian rhythms in feeding behaviour. The SnackerTracker provides a cost-effective, open-source, and user-friendly method of animal food intake and activity measurement.